Gestão de parcerias na administração pública: uma experiência no setor de telecomunicações - Carino, Luciano Oliveira (1998)
Partnership has become one of the most discussed issue all over the world, mainly through International Joint-ventures in areas of telecommunications, computer science, automobile and aerospace industry, among others. The constitution of strategic alliances by potential competitors foreseeing the exploitation of new market niches, research activities and development of new services and products, constitute innovative elements to studies on partnership. Taking for granted this exchange or synergy among partners, this work presents and it analyses the data which refers to a case study focused on professionals involved in the daily activities towards the process of companies leaders in the sectors of Telecommunications (State Company) and Network and Computer Services (Private Company). This study is structured as follows: the characterization and segmentation of the used sample (characterization of respondents); the descriptive analysis and evaluation of the representative variables of the inhibitors and facilitators factors; the differentiated perceptions of elements according to the professional experience and involvement degree with the partnership processes; the inhibitors and facilitators elements pointed as the most relevant; and the results obtained with the use of factorial technique analysis.